2012
DOI: 10.1096/fj.12-208397
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution insights into binding of unfolded polypeptides by the PPIase chaperone SlpA

Abstract: SlpA is a 2-domain protein consisting of an FK506-binding protein (FKBP) domain that harbors the peptidyl-prolyl cis/trans-isomerase (PPIase) active site and a small insert-in-flap (IF) domain that endows the protein with chaperone activity. We have determined the structure of SlpA from Escherichia coli at 1.35-Å resolution. The overall structure is similar to other known structures of the FKBP-IF subfamily. However, by serendipity, the linker region of the purification tag binds in the chaperone binding groov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 55 publications
5
27
0
3
Order By: Relevance
“…1a–d . We mainly used 15-residue-long proline-containing segments from proteins that have previously been shown to bind to TtSlyD and/or other proteins from the SlyD family, namely RNase T1, which is a model protein for folding studies, and the ribosomal proteins S2 and S3 [ 17 , 18 , 24 ]; see Table 1 for the complete list of peptide sequences. Table 2 summarizes the results of the binding studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a–d . We mainly used 15-residue-long proline-containing segments from proteins that have previously been shown to bind to TtSlyD and/or other proteins from the SlyD family, namely RNase T1, which is a model protein for folding studies, and the ribosomal proteins S2 and S3 [ 17 , 18 , 24 ]; see Table 1 for the complete list of peptide sequences. Table 2 summarizes the results of the binding studies.…”
Section: Resultsmentioning
confidence: 99%
“…The stoichiometries were, however, significantly higher than 1 after fitting to a single binding site model, indicating that these peptides may still engage both binding sites (Table 2 ). We also measured binding of an eight-residue-long peptide representing the plasmid-derived linker sequence bound to the IF domain in the crystal structure of SlpA (SlpA linker; [ 18 ]), which was found to bind with an affinity similar to that of the seven-residue-long S2-short8 peptide. We conclude that the sequence requirements for peptide binding to TtSlyD FL are rather lax, which is in part because the enthalpic losses incurred by apparent sequence mismatching are readily compensated by gains in entropy, and that the affinity of binding to both domains is sensitive to the length of the peptide (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of an FKBP-type PPIase domain and a small insert-in-fl ap (IF) domain which are responsible for its chaperone activity. It is suggested that SlpA is involved in ribosome assembly process (Quistgaard et al 2012 ).…”
Section: Bacterial Immunophilinsmentioning
confidence: 99%
“…Bacterial adhesion to epithelial and subepithelial tissue is an important initial event in successful colonization of the mammalian intestine and other tissue sites. Several adhesion molecules have been characterized for bacterial species that cause infectious diseases in humans or animals (Xiao et al 2013;Quistgaard et al 2012). However, knowledge is very limited regarding adhesion molecules present on the mammalian commensal genus Lactobacillus.…”
Section: Introductionmentioning
confidence: 99%